Pemanfaatan Sumberdaya Ikan Hasil Tangkapan Masyarakat Lokal Papua Kampung Es Wambi Distrik Okaba Kabupaten Merauke - Sunarni Sunarni; Sajriawati Sajriawati (JURNAL RISET RUMPUN ILMU HEWANI, 2025)
This study aims to determine the types of fish caught by the local community of Es Wambi village and how the local community of Es Wambi village utilizes the fish caught. The study was conducted from May to July 2024, in Es Wambi village, Okaba District, Merauke Regency. The sampling technique used in this study was non-probability sampling. Data collection techniques used observation, interview, and questionnaire techniques. The results of the study found that the types of fish caught by the local community consisted of 11 types from sea waters and 4 types from fresh waters. Types of fish from sea waters are; stingray (Dasyatis sp), ribbonfish (Trisiulus savala), kuro fish (Eleutheronema tetradactylum), bulanak fish (Mugil chepalus), gulama fish (Jhonius sp), snapper (Lates calcarifer), glass fish (Kurtus guliferi), bambit fish (Selenotoca sp), thorn fish (Chinetodus sp), julung-julung fish (Strongylura-strongylura) and tongue fish (Cynoglassus lingua). Meanwhile, the fish caught from fresh waters are; tilapia (Oreochromis mossambicus), betik fish (Anabas Testudineus), snakehead fish (Chana striata) and tilapia (Oreochromis niloticus). The utilization of fish caught by local people based on observation results is grouped into 3 parts, namely used as consumption fish, sold fresh and processed into salted fish.